EVALUASI EFISIENSI PANAS DAN EMISI GAS RUMAH KACA PADA ROTARY KILN PABRIK SEMEN - Farisa Ridha Mutiara; Hadiyanto Hadiyanto (Diponegoro University, 2013)
Kiln is an equipment which has vital existence in the manufacture of cement. Kiln firing requires a hightemperature to produce a clinker. Higher combustion temperature allows heat transfer occurs on the surfacecoating on the walls of the kiln that is not evenly distributed, so most of the heat is absorbed. As a consequence,it requires large amounts of fuel. Heat efficiency in the kiln is important to know. Production of clinker in thekiln which occurs at high temperatures, will also release a variety of gases, such as CO2. Carbon dioxide isincluded as one of the greenhouse gas, this gas will negatively impact the earth's ozone. Therefore, need to knowthe range of greenhouse gas that is formed, in order to determine the appropriate mitigation and prevention.Evaluation result of heat efficiency in the kiln is 43,17% by generating greenhouse gas emissions amounted to6,173 tonnes CO2 equivalent / tonne of coal.